Implementation of Sharia Business Management in Financial Management at Warasansart Lammai School, Thailand - Marisa, Mawar; Amsari, Syahrul (Economics and Digital Business Review, 2026)
Sharia-based financial management is a strategic aspect for the sustainability of Islamic educational institutions, particularly within Muslim minority communities. This study aims to analyze the implementation of Sharia business management in financial management at Warasansart Lammai School, Thailand, and to identify its supporting and inhibiting factors. The research employs a descriptive qualitative approach with a case study design through observation, in-depth interviews, and documentation, analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that the values of amanah (trustworthiness) and transparency have been implemented; however, they are not yet optimal due to the use of manual recording systems, unstructured separation of Sharia funds, and limited human resource understanding of Sharia contracts. This study concludes that the implementation of Sharia business management is still at an early stage and requires strengthening through the development of Sharia financial standard operating procedures (SOP), enhancement of human resource capacity, and the development of more transparent and accountable reporting systems.